Delimitación del pit final mediante el modelo matemático flujo máximo pseudoflow en minas a tajo abierto, 2023 - Marquina Araujo, Jairo Jhonatan (2023)
The main objective of the research was to delimit the final pit using the maximum flow pseudoflow mathematical model in an open-pit mine, 2023. The methodology employed was non-experimental, descriptive, and applicative design. The population consisted of all block models from open-pit mines, and the sample consisted of the block model from one open-pit mine. To validate the hypothesis, quality control was used with a significance level of 5%. The critical value obtained was 838.72, and the F statistic was 5.14. The results revealed that the block model consisted of 480,000 blocks with dimensions of 10x10x10 m, and the copper grade ranged from 0% to 1.41%. The necessary parameters for the delimitation of the final pit were determined, including a slope angle of 45°. In financial terms, values such as the base copper price of 3.9 US$/lb, smelting cost of 0.4 US$/lb, mining cost of 2.3 US$/ton, crushing and milling cost of 11 US$/ton, and a metallurgical recovery of 90% were considered. Multiple pit scenarios were generated, incorporating variations in the product price. In total, 20 pits were created with an entrance factor ranging from 0.1 to 2, with an increment of 0.1, resulting in a total net present value (NPV) of 175,929 MUS$. It was determined that pit 20 was the optimal one, with an NPV of 17,855 MUS$, 212 million tons of ore, 58 million tons of waste, and a stripping ratio (SR) of 0.27. Finally, it was concluded that pit 20 was the most optimal compared to the other generated pits. This selection was based on its high NPV and a lower SR, ensuring economic viability.